2018
DOI: 10.22581/muet1982.1804.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Time on Nickel Aluminide Coating Deposition

Abstract: The βNiAl coating was deposited onto Nickel based CMSX-4 superalloy by in-situ CVD (Chemical Vapor Deposition) method. Main focus of this contribution was to study the influence of aluminizing time and temperature on the microstructure and thickness of the coating; this was followed by examination by XRD (X-Ray Diffraction), electron microscope. Results suggest that an incremental variation in temperature alters the coating activities from HA (High Activity) to LA (Low Activity). This is exhibited by the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This rig covers with a Lead shell to avoid radiations leakage. These radiations are injurious and harmful to the living organism, exposed material and apparatus has to be dumped soon after the testing and use [4][5][6].…”
Section: Accelerated Ageingmentioning
confidence: 99%
“…This rig covers with a Lead shell to avoid radiations leakage. These radiations are injurious and harmful to the living organism, exposed material and apparatus has to be dumped soon after the testing and use [4][5][6].…”
Section: Accelerated Ageingmentioning
confidence: 99%
“…This is a common and widely used technique adopted for increasing the strength of steel. It was found that it is the most cheap and easy method of grain refinement, but during the last twenty years there was not paid attention to the fact that the nucleation sites for forming these nitride particles are more valuable regarding their effect on limiting the grain boundary movement [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…No one has given the attention that aluminum nitride particles can be useful for grain refinement technique, but it also affects the austenite formation kinetics limiting the grain boundary movement. [3,14,16,17] these riddle and unrevealed features of AlN particles have been studied in the present research work. [3, [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%